EQUITY CROWDFUNDING INDUSTRY REGULATIONS IN MALAYSIA AND INDONESIA: PROSPECTS AND CHALLENGES DURING THE COVID-19 PANDEMIC (Journal of International Studies, 2022)
Equity crowdfunding (ECF), also known as crowd-investing or investment crowdfunding, is a way of boosting capital used by start-ups and early-stage companies. Fundamentally, ECF offers the company’s securities to potential investors in exchange for their investment. As a result, each investor is authorized to a share in the company proportionate to their financing. This paper discusses the ECF industry regulations in Malaysia and Indonesia in terms of its prospects and challenges during the COVID-19 pandemic through doctrinal research using the conventional legal method. Critical and analytical approaches were used to achieve its objectives. The findings showed that ECF has seen a growth of over 170% in new accounts registered in Malaysia, with 65% of them being retail investors. There is a great demand from individual and retail investors who are looking to invest in various investment products and services made accessible to them. The Capital Markets and Services Act 2007 plays an important role to provide good governance of ECF business in Malaysia. Further, the Guidelines on Recognized Markets (GRM 2020) (Item 1.01 GRM) and section 15 (g) of the Securities Commission Act 1993 clarifies the function of the Securities Commission to regulate ECF activities and protect the interests of the parties involved, especially investors. In Indonesia, the main regulator of ECF is the Financial Services Authority and the new ECF law is the Financial Services Authority Regulation Number 57/POJK.04/2020 concerning Securities Crowdfunding. The regulation aims to extend the scope of the crowdfunding which includes debt-based securities and sukuk. The prospects of ECF business in both countries are great especially in the era of the pandemic because the fintech, which has led to new investment products and services, is a vital force that helps democratize investments and will continue to increase as investors become more educated and informed. In terms of the ECF law, comparatively, it is different in terms of the governance, process and procedure, types of investors, etc. which are applicable in both Malaysia and Indonesia.